2018
DOI: 10.1093/ntr/nty169
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Price on the Consumption of Reduced Nicotine Cigarettes

Abstract: The FDA has proposed a rule that would reduce nicotine content in commercially available cigarettes. However, it is not known how smokers may respond in an environment where products of differing nicotine content and of differing prices are available. This study demonstrates that price may be an important factor that could lead smokers to select reduced nicotine products voluntarily, even if those products are rated as inferior or less satisfying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Studies showed higher demand for regular cigarettes compared to VLNCs, particularly among more dependent smokers and those not motivated to quit. 45,46,60 However, there was a significant effect of cost, with increased cost of regular cigarettes (alongside a constant price of VLNCs) resulting in greater demand for VLNCs, 60,76 suggesting demand for VLNCs may increase as it becomes more difficult to obtain conventional cigarettes. A large double-blind RCT comparing usual brand cigarette with six different VLNC conditions found that reduced nicotine decreased the number of cigarettes people estimated they would smoke and increased the number of smokers who reported they would not smoke across a range of prices.…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed higher demand for regular cigarettes compared to VLNCs, particularly among more dependent smokers and those not motivated to quit. 45,46,60 However, there was a significant effect of cost, with increased cost of regular cigarettes (alongside a constant price of VLNCs) resulting in greater demand for VLNCs, 60,76 suggesting demand for VLNCs may increase as it becomes more difficult to obtain conventional cigarettes. A large double-blind RCT comparing usual brand cigarette with six different VLNC conditions found that reduced nicotine decreased the number of cigarettes people estimated they would smoke and increased the number of smokers who reported they would not smoke across a range of prices.…”
Section: Resultsmentioning
confidence: 99%
“…These consumers tend to consume the same amount of nicotine on a daily basis to achieve desired effects, adjusting consumption to compensate for the difference in nicotine availability when using low-quality cigarettes [28,30]. These data are consolidated with the survey carried out by the Brazilian Institute of Ethics in Competition [2], which points out that smuggled cigarette consumers consume two more units per day compared to legal cigarette consumers.…”
Section: Application Of the Optimized Methods To Real Samplesmentioning
confidence: 99%
“…Similarly, low nicotine cigarettes maintain higher breakpoints on progressive ratio schedules of reinforcement relative to not smoking (Rusted et al, 1998;Donny et al, 2007). Finally, when using purchase tasks to assess the economic demand of simultaneously available low and normal nicotine content cigarettes, escalating the price of regular nicotine content cigarettes increases the demand for low nicotine cigarettes presented at a fixed price (Johnson, Bickel, & Kirshenbaum, 2004;Higgins et al, 2017b;Branstetter et al, 2019). This cross-product elasticity suggests the relative value of low nicotine cigarettes is not zero and may increase as usual cigarettes become more difficult to acquire.…”
Section: Limited Spontaneous Cessation Observed After Extended Usementioning
confidence: 99%